Microplastic in Sediment from the Middle Segment of an Urban River of Samarinda City, East Kalimantan - Saputri, Dea; Hamdhani, Hamdhani; Suryana, Irma (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2023)
The increasing use of plastic causes an increase in plastic waste in the environment, especially waters. Plastic waste that enters the waters will then be degraded into polymers less than 5 mm called as microplastics.  The purpose of this study was to determine the content of microplastics and sediment and the relationship between microplastics in sediment in an urban river of Samarinda City. Sampling was carried out at 3 stations, then sample analysis was carried out at the Water Quality Laboratory of Mulawarman University. Based on the results of the research obtained, the types of microplastics found are fiber, fragments, films and microbeads. The most type of microplastic was found is film. The mean concentration of microplastic in the sediment was 1322,22 particles/kg.